Utility of Washington Early Recognition Center Self-Report Screening Questionnaires in the Assessment of Patients with Schizophrenia and Bipolar Disorder - Hsieh, Christina J.; Godwin, Douglass; Mamah, Daniel (Frontiers in Psychiatry, 2016)
Early identification and treatment are associated with improved outcomes in bipolar disorder and schizophrenia. Screening for the presence of these disorders usually involves time-intensive interviews that may not be practical in settings where mental health providers are limited. Thus, individuals at earlier stages of illness are often not identified. The Washington Early Recognition Center Affectivity and Psychosis (WERCAP) Screen is a self-report questionnaire originally developed to identify clinical risk for developing bipolar or psychotic disorders. The goal of the current study was to investigate the utility of the WERCAP Screen and two complementary questionnaires, the WERC Stress Screen and the WERC Substance Screen, in identifying individuals with established schizophrenia or bipolar disorder. Participants consisted of 35 bipolar disorder (BPD) and 34 schizophrenia (SCZ) patients, as well as 32 controls (CON), aged 18-30 years. Univariate analyses were used to test for score differences between groups. Logistic regression and ROC curves were used to identify diagnostic predictors. Significant group differences were found for the psychosis section of the WERCAP (pWERCAP; p < 0.001), affective section of the WERCAP (aWERCAP; p = 0.001), and stress severity (p = 0.027). No significant group differences were found in the rates of substance use as measured by the WERC Substance Screen (p = 0.267). Only the aWERCAP and pWERCAP scores were useful predictors of diagnostic category. ROC curve analysis showed the optimal cut-point on the aWERCAP to identify bipolar disorder among our participant groups was a score of >20 (AUC: 0.87; sensitivity: 0.91; specificity: 1.0); while that for the pWERCAP to identify schizophrenia was a score of >13 (AUC: 0.89; sensitivity: 0.88; specificity: 0.88). These results indicate that the WERCAP Screen may be useful in screening individuals for bipolar disorder and schizophrenia, and that identifying stress and substance use severity can be rapidly done using self-report questionnaires. Larger studies in undiagnosed individuals will be needed to test the WERCAP Screen’s ability to identify mania or psychosis in the community.